Arabidopsis floral homeotic gene BELL (BEL1) controls ovule development through negative regulation of AGAMOUS gene (AG). - Ray, A (1994)
Ovules are the developmental precursors of seeds. In angiosperms the ovules are enclosed within the central floral organs, the carpels. We have identified a homeotic mutation in Arabidopsis, "bell" (bel1), which causes transformation of ovule integuments into carpels. In situ hybridization analysis shows that this mutation leads to increased expression of the carpel-determining homeotic gene AGAMOUS (AG) in the mutant ovules. Introduction of a constitutively expressed AG transgene into wild-type plants causes the ovules to resemble those of bel1 mutants. We propose that the BEL1 gene product directs normal integument development, in part by suppressing AG expression in this structure. Our results allow expansion of the current model of floral organ identity to include regulation of ovule integument identity.